2012
DOI: 10.1128/aac.05198-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of Innate Immune Receptors in Paradoxical Caspofungin ActivityIn Vivoin Preclinical Aspergillosis

Abstract: This study investigated the possible mechanisms underlying the paradoxical caspofungin activity in vivo in preclinical aspergillosis. We evaluated the activity of escalating doses of caspofungin in vivo in different preclinical models of invasive aspergillosis, including mice deficient for selected innate immune receptors. The therapeutic efficacy of caspofungin in experimental invasive aspergillosis was strictly dose dependent, being observed at doses of 0.1 and 1 mg/kg of body weight depending on the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…Previous studies detailed the in vitro “paradoxical effect” of fungal growth in the presence of high levels of caspofungin (20, 54), and a recent study demonstrated increased chitin synthase activity and fungal stress response activation in response to caspofungin that permits A. fumigatus growth despite the presence of drug-mediated cell wall remodeling (55). These in vitro results are supported by in vivo evidence from Moretti et al that demonstrated decreased caspofungin efficacy in mice with IA (20, 40). Similar to our results, they reported mouse strain-dependent differences in fungal burden, with BALB/c mice most susceptible to infection at any dose of caspofungin, and C57BL/6 mice exhibiting a drug dose-dependent response.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Previous studies detailed the in vitro “paradoxical effect” of fungal growth in the presence of high levels of caspofungin (20, 54), and a recent study demonstrated increased chitin synthase activity and fungal stress response activation in response to caspofungin that permits A. fumigatus growth despite the presence of drug-mediated cell wall remodeling (55). These in vitro results are supported by in vivo evidence from Moretti et al that demonstrated decreased caspofungin efficacy in mice with IA (20, 40). Similar to our results, they reported mouse strain-dependent differences in fungal burden, with BALB/c mice most susceptible to infection at any dose of caspofungin, and C57BL/6 mice exhibiting a drug dose-dependent response.…”
Section: Discussionsupporting
confidence: 55%
“…In addition to reporting increased mouse fungal burden in IA after caspofungin therapy, Moretti et al also provided mechanistic data that demonstrated a requirement for TLR2, TLR9, and Dectin-1 (40). Interestingly, TLR2 and TLR9 expression were required for macrophage secretion of IL-17A and IL-10 in response to purified chitin particles (56, 57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, after introduction of CAS in clinical trials, no decrease in the mortality rate of patients with invasive aspergillosis was reported (6). Apparently, there are at least two drawbacks: (i) the increasing resistance against CAS (7) and (ii) the so-called paradoxical effect leading to attenuated activity of echinocandin antifungals at high concentrations (8,9). However, echinocandins still show promising features as the basis for a combined antifungal therapy because they are poor substrates for cytochrome (CYP) P450 enzymes and P-glycoproteins (10).…”
mentioning
confidence: 99%